Preventive Care Needs of the North Carolina Medicaid Expansion Population - Jennifer C. Spencer, PhD; Rebecca G. Whitaker, PhD; Michael P. Pignone, MD, MPH (Elsevier, 2025)
Introduction: Effective December 2023, North Carolina expanded Medicaid eligibility to cover individuals up to 138% of the Federal Poverty Level. The authors sought to understand the preventive care needs of the newly Medicaid-eligible population. Methods: The authors conducted a repeat cross-sectional analysis using the 2016, 2018, 2020, and 2022 North Carolina Behavioral Risk Factor Surveillance Survey. The authors defined the Medicaid expansion population as those aged 18-64 years with household incomes below 138% Federal Poverty Level and reporting no current source of insurance. The authors compared with those enrolled in traditional Medicaid and all nonelderly adult North Carolinians, evaluating up-to-date use of preventive care services. Survey weights were used to estimate total unmet need. Results: The authors estimated 294,000 individuals in the Medicaid expansion population in 2022. Preventive care use was low for the expansion population in all years. In 2022, 36.7% (27.7%-46.8%) reported having a regular source of care, 40.2% (31.1%-50%) reported a past-year wellness visit, and 45.7% (36.6%-55.2%) reported delaying needed care owing to cost. Among eligible respondents, 28.6% (13.8%-50.2%) were up to date with colorectal cancer screening (vs 49.4% [30.5%-68.4%] for traditional Medicaid and 71% [67.3%-74.4%] for all North Carolina population). It was estimated that 176,000 in the expansion population needed a wellness visit; 186,000 needed a regular care provider; and 66,000 needed 1 or more cancer screening. Conclusions: The North Carolina Medicaid expansion population has a high number of unmet preventive care needs. North Carolina should consider approaches to improve provider capacity for those in Medicaid and promote preventive care and risk reduction for the newly enrolled expansion population.